2013
DOI: 10.1021/mp400263d
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of Spray-Dried Microspheres Consisting of PLGA and PVP: Relating the Influence of Heat and Humidity to the Thermal Characteristics of These Polymers

Abstract: In view of the increasing interest in injectable controlled release formulations for the treatment of chronic diseases, injectable polymeric microspheres consisting of a surface layer of poly(lactic-co-glycolic acid) (PLGA) and an underlying polyvinylpyrrolidone (PVP) layer were previously developed. The present study focuses on the influence of heat and humidity on the surface characteristics of these spray-dried PLGA/PVP microspheres. The response of the polymeric matrix to these factors will provide an insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…The spatial distribution of the API and PLGA at the sample surface is represented in Figure 4. There is a negligible amount of PVP observed at the particle surface which is consistent with previous studies (8,9) and depicted in Figure 2 of the Supplementary Information. At the micron-scale resolution of the ToF-SIMS data the drug seems to be homogeneously distributed at the surface of the three model formulations.…”
Section: Surface Chemical Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…The spatial distribution of the API and PLGA at the sample surface is represented in Figure 4. There is a negligible amount of PVP observed at the particle surface which is consistent with previous studies (8,9) and depicted in Figure 2 of the Supplementary Information. At the micron-scale resolution of the ToF-SIMS data the drug seems to be homogeneously distributed at the surface of the three model formulations.…”
Section: Surface Chemical Analysissupporting
confidence: 91%
“…In addition, the absence of a T g around 56°C (T g of the API) indicates that the API is molecularly dispersed in a phase separated system made up of a PLGA-rich phase and a PVP-rich phase. Preceding work has already revealed that hollow spheres are formed when PLGA and PVP are spray-dried together with a PLGA surface layer and an underlying PVP layer (8,9). The presence of PLGA at the particle surface is due to its surface activity and a consequence of restructuring of the methyl side groups of PLGA towards the droplet-air surface (8,19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations